Fetal spina bifida associates with dysregulation in nutrient‐sensitive placental gene networks: Findings from a matched case–control study - Marina White; Jayden Arif‐Pardy; Tim Van Mieghem; Kristin L. Connor (Clinical and Translational Science, 2024)
Abstract To improve outcomes in fetuses with spina bifida (SB), better understanding is needed of the molecular drivers of SB and its comorbidities. Pregnant people carrying a fetus with isolated SB (cases; n = 12) or a fetus with no congenital anomalies (controls; n = 21) were recruited at Mount Sinai Hospital, Toronto, Ontario, Canada. Clinical data and placental samples were collected. Placental transcriptome was sequenced (Clariom D microarray) and a nutrient‐focused gene expression analysis pipeline was applied to determine whether fetal SB associates with placental dysfunction. Of the 391 differentially expressed genes (DEGs) in cases, 11% (n = 42) had at least one nutrient cofactor, including B vitamins (n = 7 genes), iron/heme (n = 6), and zinc (n = 11). Cases had dysregulation in genes not previously known to associate with SB, and in placental genes that have known links to SB but have not been previously identified in the placenta. Cases also had downregulated nutrient transport and upregulated branching angiogenesis and immune/inflammatory processes. Five nutrient‐dependent transcription regulators, collectively predicted to target 46% of DEGs in cases, were identified and were most commonly dependent on B vitamins (n = 3) and zinc (n = 2). Placental gene expression changes were most acute in cases with poor growth. Placentae from fetuses with SB have dysregulation in several gene networks, including those that are sensitive to multiple micronutrients beyond the well‐known folic acid. An improved understanding of placental phenotype in fetuses with SB may help identify novel mechanisms associated with comorbidities in fetuses with SB, and reveal new targets to improve fetal outcomes in this population.